1999
DOI: 10.1038/15207
|View full text |Cite
|
Sign up to set email alerts
|

Chronic brain inflammation and persistent herpes simplex virus 1 thymidine kinase expression in survivors of syngeneic glioma treated by adenovirus-mediated gene therapy: Implications for clinical trials

Abstract: The long-term consequences of adenovirus-mediated conditional cytotoxic gene therapy for gliomas remain uncharacterized. We report here detection of active brain inflammation 3 months after successful inhibition of syngeneic glioma growth. The inflammatory infiltrate consisted of activated macrophages/microglia and astrocytes, and T lymphocytes positive for leucosyalin, CD3 and CD8, and included secondary demyelination. We detected strong widespread herpes simplex virus 1 thymidine kinase immunoreactivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
225
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(232 citation statements)
references
References 38 publications
3
225
1
3
Order By: Relevance
“…Adenoviral vectors are highly efficient at in vivo transduction and can be concentrated to high titers, thus it is possible to stereotactically inject high titers of viruses directly into the area of brain infiltrated by tumor cells. [17][18][19] In addition to the high efficiency of transduction, adenoviruses mediate high-level transgene expression and pose little risk of insertional mutagenesis.…”
Section: Ecorin Plays Different Roles In Regulating Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviral vectors are highly efficient at in vivo transduction and can be concentrated to high titers, thus it is possible to stereotactically inject high titers of viruses directly into the area of brain infiltrated by tumor cells. [17][18][19] In addition to the high efficiency of transduction, adenoviruses mediate high-level transgene expression and pose little risk of insertional mutagenesis.…”
Section: Ecorin Plays Different Roles In Regulating Matrixmentioning
confidence: 99%
“…17,[20][21][22][23] We have assessed this for up to 3 months after CNS-1 tumor implantation in the survivors after gene therapy using RAd/HSV1-TK plus ganciclovir. The reasons for this are two-fold.…”
Section: Ecorin Plays Different Roles In Regulating Matrixmentioning
confidence: 99%
“…9 Success of this approach in animal tumor models has led to clinical trials in a variety of tumor types. [22][23][24][25] An important feature of this form of enzyme-prodrug therapy is that HSV-TK-expressing cells can cause GCVmediated cytotoxicity in tumor cells that do not express the transgene, a process known as the bystander effect. 10,[26][27][28] Bystander cytotoxicity is critical for the enzyme-prodrug gene therapy strategy because current techniques for gene transfer typically result in fewer than 10% of the cells expressing the transgene.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a recent study reported widespread chronic brain inflammation, vector distribution, and detection of TK protein in animals cured of experimental gliomas by local injection of replication-incompetent adenoviral TK vectors in combination with systemic GCV treatment. 28 Hence, the occurrence of acute and chronic inflammation and their effects in response to HSV-based TK/GCV therapy are important areas of future investigation.…”
Section: Discussionmentioning
confidence: 99%